ADHESION OF LACTIC ACID BACTERIA (LAB) TO INTESTINAL EPITHELIAL CELLS OF RED SNAPPER (Lutjanus argentimaculatus) IN INHIBITING Vibrio alginolyticus - Gavion Roston Sitepu; Nursyirwani '; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from November 2015 until March 2016 in the Marine Microbiology Laboratory and in the Laboratory of Aquaculture Enviromental Quality of in the Faculty of Fishery and Marine Science, Riau University. The purpose of this research was to determine the adhesion ability of Lactic Acid Bacteria (LAB) isolates on intestinal epithelial celss of red snapper (L. argentimaculatus) and in inhibiting adhesion of V. alginolyticus. Completely randomized design (CRD) method was performed in this experimental research. Two factors treated were three LAB isolates (KP 1, KP 2, KP 3 and concertio) and V. alginolyticus. Three adhesion methods applied were competitive, competition and displacement. Adhesion of bacteria to the epithelial cells was calculated based on number of bacterial cells adhered. The results showed that all LAB isolates had higher adhesion ability than V. alginolyticus. Isolate concertio indicated the highest adhesion ability (52.67±7.76 cells/epithelial cells) to the epithelial cells and the lewest was indicated by isolate V. alginolyticus (23.11±2.79 cells/epithelial cells). However, the inhibition ability of the three LAB isolates upon V. alginolyticus by the three adhesion methods was not significantly different.Keywords: Adhesion, Lactic acid bacteria (LAB), V. alginolyticus, Intestinal epithelial cells, red snapper.